This study was conducted in January 2020, located in Api-api Village, Bandar Laksamana District, Bengkalis. The purpose of this study was to determine the effect of the total organic of sediment content on the density of bamboo clam (S. lamarckii), in the - Zulkifli, Muhammad; Nasution, Syafruddin; Efriyeldi, Efriyeldi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2020)
This study was conducted in January 2020, located in Api-api Village, Bandar Laksamana District, Bengkalis. The purpose of this study was to determine the effect of the total organic of sediment content on the density of bamboo clam (S. lamarckii), in the intertidal zone. The method used in this study was a survey method. The results show that the content of organic sediment was relatively low with an average of 1.28%. The density of bamboo clam that ia found mostly in subzone 1 with the number 25 ind. The most frequent distribution of bamboo clam sizes is in the range of 5.0-5.4 cm with 56 inds. The relationship of organic sediment content with the density of bamboo clam is very weak with r = 0.1519 and R2 = 2.31%